Exploring Chinese college students' construction of online identity on the Sina Microblog. (December 2018) - Yuan, Zhou-min
Highlights: Chinese college student microblog users tend to use more implicit identity claims. Situation-appropriate multiple identities are strategically constructed. The user, displayed friends and distant audiences triangulate to mould identities. Online identity should be understood as a dual mechanism to create identity rhetoric. The split of the virtual world and the real world has been increasingly blurred. Abstract: This paper aims to investigate identity construction on a social network site, the largest microblog platform, Sina Microblog, in China. By focusing on the action types and language use in the status updates and personal profiles of ten college student users from China together with individual interviews, this study finds that microblog users employ a variety of strategies to construct their online identities, such as different action types; visual, enumerative, narrative and self-labelling practices; and different forms of internet language. The results also show that microblog users tend to use more implicit identity claims and strategically use language to construct situation-appropriate multiple identities, using identity rhetoric to achieve some communicative needs. The user, displayed friends and distant audiences triangulate to mould and portray their online identities on the Sina Microblog. The related factors that shape identity construction are described, and the implications of these findings are discussed.